ASOSIASI KOMUNITAS MAKROZOOBENTOS PADA PADANG LAMUN DI PERAIRAN PULAU PANJANG KEPULAUAN DERAWAN - Muhamad Roem; Andi Niar; Dori Rachmawani (Jurusan Akuakultur, Universitas Bangka Belitung, 2022)
Macrozoobentos is one of the basic organisms of waters associated with the seagrass ecosystem. This study aims to determine the correlation between the density of Macrozoobentos and seagrass cover in the seagrass ecosystem in the waters of Panjang Island. Sampling was done during lowest tide periode by a quadrat transect method consisting of 3 transects and spanned 50 from coral reefs to coastal areas. The results obtained 83 Type Macrozoobentos of 8 Classes with a total of 4,097 ind. The type of seagrass found on Pulau Panjang consists of Cymodocea rotundata, Thalassia hemprichii, Halophila ovalis, Halodule uninervis, Syringodium isoetifolium and Enhalus acoroides, average seagrass density of 6 stations in Panjang Island waters ie Thalassia hemprichii 644 / m2 and The lowest is the seagrass type Enhalus acoroides 76 stands / m2.